Forensic Psychiatric Evaluation and Communication with the Child - Güler, Gülen; Yıldırım, Veli; Kütük, Meryem Özlem; Toros, Fevziye (The Bulletin of Legal Medicine, 2016)
There are many different key points of forensic interview from clinic interview in child and adolescent psychiatry clinical practice. The primary task of the forensic interviewer is to express medical opinion about the request of person, court or institution to evaluate the patient, rather than treating him. In the world and in our country, number of criminal cases involving children and adolescents are gradually increasing. In an effective forensic psychiatric evaluation; so many factors must be considered such as child’s age, the duration and the number of the negotiations, intrafamilial parent’s conflicts, psychosocial developmental stage of the children and psychopathology of the parents. Ineffective forensic psychiatric evaluations can lead false claims in legal proceedings, increased stress on the family and child, distortion of facts and an increase or decrease in the conviction. To ensure effectiveness of forensic psychiatric evaluations in child age group, understanding of children developmental processes and conducting age-sensitive communication are of special importance. In this review, communication with child, especially sexual abuse cases and forensic psychiatric assessment, will be discussed in the light of current knowledge.Keywords: Adolescent; Communication; Child; Forensic interview; Sexual abuse.
Keywords: adolescent; communication; child; forensic interview; sexual abuse